The Soloist [videorecording] - Wright, Joe 1972-; Foxx, Jamie (Dreamworks Home Entertainment, 2009)
Los Angeles Times reporter Steve Lopez discovers Nathaniel Anthony Ayers, a former classical music prodigy, playing his violin on the street of L.A. A unique friendship is formed, one that transforms both their lives.